2004
DOI: 10.1016/j.jom.2004.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The labor–machine dyad and its influence on mix flexibility

Abstract: The joint, mediating, and interactive effects of three elements of labor and machine flexibility on mix flexibility were tested empirically in a PCB assembly plant. Both subjective and objective data were collected. Some elements of labor and machine flexibility mediated the relationship between an emphasis on competitive priorities and mix flexibility. The interactive effects of machine and labor flexibility on mix flexibility confirmed prior findings that the pursuit of total flexibility is not desirable. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 95 publications
(190 reference statements)
1
13
0
Order By: Relevance
“…Mendelson and Pillai (1999) found a steady decrease (average 9.4% per year) in the duration of product life cycles in several industry segments over the period from 1988 to 1995. Similar trends appear to affect requirements in product mix (Kekre and Srinivasan, 1990; Karuppan and Ganster, 2004), and demand volume (Suarez et al, 1996; Jack and Raturi, 2002).…”
Section: Introductionmentioning
confidence: 83%
“…Mendelson and Pillai (1999) found a steady decrease (average 9.4% per year) in the duration of product life cycles in several industry segments over the period from 1988 to 1995. Similar trends appear to affect requirements in product mix (Kekre and Srinivasan, 1990; Karuppan and Ganster, 2004), and demand volume (Suarez et al, 1996; Jack and Raturi, 2002).…”
Section: Introductionmentioning
confidence: 83%
“…All variables have been considered as reflective variables as related literature has treated them (see Karuppan andGanster, 2004 andChang et al, 2006 for manufacturing flexibility, Yalcinkaya et al, 2007 andPatel et al, 2012 for exploration and exploitation strategies, or Ruiz, Molina, and Lloréns (2009) for organizational learning).…”
Section: Methodsmentioning
confidence: 99%
“…Outside the simulated experiments and anecdotes, systematic empirical examination of the association between labor flexibility and firm performance seems to be scarce (Beltran‐Martin et al, 2008; Bhattacharya et al, 2005; Karuppan and Ganster, 2004) and provide inconsistent results (Arvanitis, 2005). Some studies have found supporting evidence (Beltran‐Martin et al, 2008; Black and Lynch, 2000; Youndt et al, 1996) and others have found evidence negating the association between labor flexibility and plant performance (Godard, 2004; Schultz et al, 2003; Valverde et al, 2000), thus rendering the topic open for further inquiry.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…For example, strategy theorists have examined it in the context of resource based theory, human resource theorists have examined it as numerical versus functional flexibility, economists have examined it in the context of labor market analysis, and operations management researchers have examined it from the process design perspective. Despite its conceptual attractiveness, the empirical research is sparse (Aksin and Karaesmen, 2007; Bhattacharya et al, 2005; Karuppan and Ganster, 2004; Upton, 1995) and the results are conflicting (Arvanitis, 2005; Schultz et al, 2003; Pinker and Shumsky, 2000). These inconsistent results suggest that acquiring labor flexibility does not automatically translate to better plant performance, an observation also made by Upton (1995) in a case study of the paper industry.…”
Section: Introductionmentioning
confidence: 99%